2011
DOI: 10.4103/0970-2113.83971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upper body resistance training on pulmonary functions in sedentary male smokers

Abstract: Background:Cigarette smoking is well correlated with lung diseases such as chronic obstructive pulmonary disease. It is common among men than women in India. In addition, sedentary lifestyle is associated with less efficient pulmonary function. Effectiveness of upper body resistance training (UBRT) in improving pulmonary function is unclear. Keeping all these factors in view, this study aims to examine the effect of UBRT on pulmonary function in male sedentary smokers.Materials and Methods:This study recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…For example, unlike other smoking cessation treatments (NRT, cognitive behavioral therapy), exercise reduces the risk of various smoking-related diseases (Type 2 diabetes, arterial stiffness, low bone mineral density, Linke et al, 2013;Singh et al, 2011;inflammation, Korhonen et al, 2011;COPD, Garcia-Aymerich et al, 2007) and increases cardiovascular fitness (maximum oxygen consumption [V O 2 max]); Korhonen et al, 2011), even among smokers who do not achieve complete abstinence during exercise-based interventions. In addition, neuroimaging research indicates that exercise activates brain reward circuitry and releases neurotransmitters purportedly responsible for smoking reward (epinephrine, serotonin, dopamine; Boecker et al, 2008;Bortz et al, 1981), which suggests that exercise may function as a rewarding substitute for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, unlike other smoking cessation treatments (NRT, cognitive behavioral therapy), exercise reduces the risk of various smoking-related diseases (Type 2 diabetes, arterial stiffness, low bone mineral density, Linke et al, 2013;Singh et al, 2011;inflammation, Korhonen et al, 2011;COPD, Garcia-Aymerich et al, 2007) and increases cardiovascular fitness (maximum oxygen consumption [V O 2 max]); Korhonen et al, 2011), even among smokers who do not achieve complete abstinence during exercise-based interventions. In addition, neuroimaging research indicates that exercise activates brain reward circuitry and releases neurotransmitters purportedly responsible for smoking reward (epinephrine, serotonin, dopamine; Boecker et al, 2008;Bortz et al, 1981), which suggests that exercise may function as a rewarding substitute for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, all pulmonary function parameters except FEV 1 /FVC improved significantly (p < 0.0001) in both yoga and swimming groups [39]. Besides, better pulmonary functions in subjects performing yoga as well as swimming are documented [4,40].…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant changes in pulmonary function of FEV 1 /FVC and FEV 1 values in people who performed regularly physical activity compared with sedentary people were shown [4]. Apart from that, the participants performed a four-week program who found statistically significant changes in FEV 1 and FEV 1 /FVC (3.96 vs. 0.96, p = 0.001), but there were no statistically significant changes in the FVC value (4.13, p = 0.43) [39]. This program included upper limb resistive exercises for thirty minutes, supplemented with ten minutes of breathing exercises [39].…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that there is a significant association between resistance training and increased quality of sleep (Yang, Ho, Chen & Chien, 2012); and the effects of resistance training on metabolism and body composition have been rigorously tested and are well established (Strasser, Siebert, & Schobersberger, 2010). In addition to these potential positive effects, the health benefits gained from resistance training could also be particularly helpful for smokers, as resistance training has been shown to improve lung function (Singh, Jani, John, Singh, & Joseley, 2011), blood lipids (Kelley & Kelley, 2009), and blood glucose control (Strasser, Siebert, & Schobersberger, 2010). All of these factors are known indicators of disease risk that are also significantly associated with smoking (USDHHS, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training can improve lung functioning (Singh, Jani, John, Singh, & Joseley, 2011) and is therefore monitored in this study. Lung function is assessed using a portable spirometer (Spirobank G Spirometer, Medical International Research, Inc., Waukesha, WI, USA).…”
Section: Introductionmentioning
confidence: 99%